Development of squid (Loligo pealli) snack flakes - Montesa, Maribel Luib; Quintos, Sarah V. (1993.)
This study was designed to develop a snack item using fresh squid as its basic raw material. Phase I involved the conduct of a preliminary formulation trial for the development of squid snack flakes and the definition of the optimum processing conditions for the product. A formulation and process for fish crackers were adapted and modified to come up with an initial formulation and process for the squid flakes. Three different steaming time, 45, 50 and 60 minutes at 100°C, were employed for the definition of the optimum processing conditions. The samples were subjected to sensory evaluation and the optimum processing conditions defined were a steaming time of 50 minutes at 100°C, drying temperature of 80 to 82°C until the product reaches a final moisture content of 8 to 9% and a frying time of 10 seconds at 180°C. Phase II involved the selection of a combination of ingredients and the definition of their respective levels so as to produce the most acceptable snack food. Three different formulations were made by altering the proportion of the ingredients of the product and samples were presented to sensory panelists. The most acceptable formulation for squid flakes consisted of 52% by weight squid meat, 21% water, 13% cornstarch, 11% brown sugar, 1.5% iodized salt, 1% chili powder, and 0.5% MSG. Phase III involved the translation of the production from a laboratory scale of 1 kilo raw squid to a bench scale of 5 kilos raw squid to test for the repeatability of the process and formulation. This phase also included some physico-chemical tests, microbiological tests, and cost analysis based in the bench scale production. The Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT) at 5% level of significance were used to analyze the sensory evaluation results that were obtained from the study.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Squids; Snack foods